Efeitos da temperatura e do volume de água ingerido nodesempenho durante 40 km de ciclismo com intensidade auto-regulada no calor - Moises Vieira de Carvalho (2009)
Among the main body cooling techniques that can affect the physical performance, the water ingestion has been proposed as the most practical way of attenuating the core temperature increase during prolonged exercises in the heat. Therefore, the purpose of thepresent study was to evaluate the effects of the water temperature and volume ingested on performance during self-paced 40-km cycling time trials in the heat (35ºC and 60% URA). Ten male athletes participated in the study (25,5 ± 1 years-old; 68,9 ± 2,7 kg; 1,73 ± 0,02 m; 7,3 ± 0,6 % of body fat; peak power output 341 ± 12,9 W; HRmáx 187 ± 3 bpm; VO2máx.67,20 ± 1,82 mL.kg-1.min-1). The volunteers were submitted to four experimental conditions: ad libitum 10ºC (AL10), ad libitum 37ºC (AL37), scheduled 10ºC (PRO10) and scheduled 37ºC (PRO37). The water temperatures that have characterized the treatment were 10ºC and 37ºC. In AL10 and AL37, the ingestion occurred ad libitum, registering thevolume (? mL) and the moment (? km) in which it was consumed. In the last two conditions (PRO10 and PRO37) the volunteers reproduced the same pattern of ingestion in the conditions AL10 and AL37, although in an inverted way, creating thus a control for the water volume ingested ad libitum. Differences were not observed in the time trial performance times and in the partial times (TP) in every 8 km among the experimentalconditions. However, considering the overall average of the four situations, the TP24-32km was greater than the TP0-8km. The power output, cadence and average speed were not influenced by the temperature of the ingested water. However, the power output wasgreater when the volunteers consumed smaller volume of water, for the ad libitum volumeat 37ºC. During exercise, treatment effects on blood concentration of glucose and lactate, heart rate, rating of perceived exertion, rectal temperature, mean skin temperature, mean body temperature, total sweating, sweat rate, rate of heat storage, plasma osmolality and variation of the plasma volume were not identified. The water temperature has influenced the pattern of voluntary ingestion by the athletes being the volume of consumption of cold water higher than warm water. The effectiveness of this body cooling technique did notalter performance and the level of thermoregulatory, cardiovascular and metabolic stress during self-paced exercise in the heat.